Genome-wide Characterization and Expression Analysis of the SPY Gene in Gossypium hirsutum under Salt Stress (Journal of Agriculture and Biology, 2025)
The SPINDLY (SPY) gene has garnered attention because of its role in plant stress responses, namely salt stress. It was first identified as a suppressor of gibberellic acid (GA) signaling. This study offers a comprehensive analysis of the whole genome and the expression patterns of the SPY gene in Gossypium hirsutum under situations of salt stress. To investigate SPY expression patterns and their impact on G. hirsutum salt stress response pathways, we used transcriptome analysis. Our study’s findings show that SPY is essential for controlling salt stress tolerance. Reduced salt tolerance is caused by mutations in SPY (-3), while plants that overexpress SPY (SPY-OX) have reduced survival rates when exposed to salt stress. Stress-responsive genes, including Sensitive to Dehydration20 and AREB1-1-like transcription factor, were discovered to be up-regulated in SPY-3 mutants, which increased their ability to withstand stress, according to transcriptome analysis. Conversely, SPY-OX plants showed decreased expression of genes that respond to stress, which suggests that salt stress is negatively affecting their capacity to withstand it. Moreover, the increase of the CKX3 gene in SPY mutants, which suggests a reduction in cytokinin signaling, highlighted the importance of SPY in cytokinin signaling pathways. Our research provides significant understanding of how the SPY gene controls pathways related to G. hirsutum’s salt stress response. This demonstrates the significance of the gene for agricultural resilience and plant stress physiology.